Exhaust gas purification catalyst

By optimizing the balance of OSC materials with different oxygen absorption and release rates in upstream and downstream catalyst layers, the catalyst enhances OSC performance while maintaining exhaust gas purification efficiency.

JP7600910B2Active Publication Date: 2024-12-17TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021112149
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-06
Publication Date
2024-12-17
Estimated Expiration
2041-07-06

AI Technical Summary

Technical Problem

Conventional exhaust gas purification catalysts face challenges in achieving both high exhaust gas purification performance and OSC performance simultaneously, as increasing the amount of OSC materials can reduce catalyst activity.

Method used

The catalyst is designed with an upstream catalyst layer and a downstream catalyst layer, each containing specific ratios of OSC materials with different oxygen absorption and release rates, optimizing their balance to enhance OSC performance while maintaining purification efficiency.

Benefits of technology

The catalyst achieves improved OSC performance while maintaining exhaust gas purification performance by efficiently utilizing two types of OSC materials with optimized ratios in each layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600910000002
    Figure 0007600910000002
  • Figure 0007600910000003
    Figure 0007600910000003
  • Figure 0007600910000004
    Figure 0007600910000004
Patent Text Reader

Abstract

To provide an exhaust gas purifying catalyst having improved OSC performance while maintaining exhaust gas cleaning performance.SOLUTION: A exhaust gas purifying catalyst having a substrate 11 and at least one catalyst layer 12 formed on the substrate, in which an uppermost catalyst layer 14 comprises: a catalyst metal; a first OSC material having a pyrochlore structure; a second SOC material higher in oxygen absorption and release speed than the first SOC material; an upstream catalyst layer 15 formed on an upstream side of a flow direction of an exhaust gas; and an a downstream side catalyst layer 16 formed on a downstream side in a flow direction of the exhaust gas. In the upstream side catalyst layer 15, a mass ratio of the second OSC material to a total mass of the first OSC material and the second OSC material is 0.55 to 0.73. In the downstream side catalyst layer 16, the mass ratio of the second OSC material to the total mass of the first OSC material and the second OSC material is 0.27 to 0.55.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for purifying exhaust gas. [Background technology]

[0002] Exhaust gas emitted from internal combustion engines of automobiles and other vehicles contains harmful components such as carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NOx), and these harmful components are purified by exhaust gas purification catalysts before being released into the atmosphere. Conventionally, three-way catalysts that simultaneously oxidize CO and HC and reduce NOx have been used for exhaust gas purification catalysts, and those containing precious metals such as platinum (Pt), palladium (Pd), and rhodium (Rh) as catalytic metals have been widely used.

[0003] In order to efficiently purify harmful components in exhaust gas using such a three-way catalyst, the air-fuel ratio (A / F), which is the ratio of air to fuel in the mixture supplied to the internal combustion engine, must be close to the theoretical air-fuel ratio (stoichiometric). However, the actual air-fuel ratio, depending on the driving conditions of the vehicle, can be rich (excess fuel: A / F<14.7) or lean (excess oxygen: A / F>14.7) around stoichiometric, and the exhaust gas also becomes rich or lean accordingly.

[0004] In recent years, in order to improve the exhaust gas purification performance of three-way catalysts against fluctuations in the oxygen concentration in exhaust gas, inorganic materials having oxygen storage capacity (OSC) are used in the catalyst layers of exhaust gas purification catalysts. When the mixture is lean and the oxygen concentration in the exhaust gas is high (lean exhaust gas), the OSC material stores oxygen to facilitate the reduction of NOx in the exhaust gas, and when the mixture is rich and the oxygen concentration in the exhaust gas is low, the OSC material releases oxygen to facilitate the oxidation of CO and HC in the exhaust gas.

[0005] Ceria-zirconia composite oxides are widely used as OSC materials. It is also known that the OSC performance and exhaust gas purification performance can be adjusted by combining two types of OSC materials with different oxygen absorption and release rates.

[0006] As an example of such a case, Patent Document 1 describes a catalyst for purifying exhaust gas in which an OSC material having a pyrochlore structure and an OSC material having a faster oxygen absorption and release rate than the OSC material having the pyrochlore structure are used in combination at predetermined contents in the uppermost layer of a catalyst coating layer.

[0007] Here, for example, when a ceria-zirconia composite oxide is used as the OSC material, cerium exhibits OSC performance, but it reduces the activity of the catalytic metal, which may cause a decrease in exhaust gas purification performance. For this reason, if the amount of OSC material is increased to increase the OSC performance, the exhaust gas purification performance decreases. In this way, it has been difficult to improve the OSC performance while maintaining the exhaust gas purification performance in an exhaust gas purification catalyst using an OSC material. The exhaust gas purification catalyst described in Patent Document 1 has excellent exhaust gas purification performance, OSC performance, and pressure loss, but there is room for improvement in terms of achieving both exhaust gas purification performance and OSC performance. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2019-84467 A Summary of the Invention [Problem to be solved by the invention]

[0009] As described above, in conventional exhaust gas purification catalysts that use two types of OSC materials with different oxygen absorption and release rates, there is room for improvement in terms of both exhaust gas purification performance and OSC performance. Therefore, the object of the present invention is to provide an exhaust gas purification catalyst that has improved OSC performance while maintaining exhaust gas purification performance. [Means for solving the problem]

[0010] As a result of examining various means for solving the above problems, the inventors have found that the OSC performance can be improved by configuring the uppermost catalyst layer with an upstream catalyst layer and a downstream catalyst layer and optimizing the balance between two types of OSC materials with different oxygen absorption and release rates in the upstream catalyst layer and the downstream catalyst layer, and have completed the present invention.

[0011] That is, the gist of the present invention is as follows. (1) A catalyst for purifying exhaust gas, comprising a substrate and at least one catalyst layer formed on the substrate, the uppermost catalyst layer includes a catalyst metal, a first OSC material having a pyrochlore structure, and a second OSC material having a faster oxygen absorption / release rate than the first OSC material, and is composed of an upstream catalyst layer formed on the upstream side in the exhaust gas flow direction, and a downstream catalyst layer formed on the downstream side in the exhaust gas flow direction; In the upstream catalyst layer, a mass ratio of the second OSC material to a total mass of the first OSC material and the second OSC material is 0.55 to 0.73; In the downstream side catalyst layer, a mass ratio of the second OSC material to a total mass of the first OSC material and the second OSC material is 0.27 to 0.55. Catalyst for purifying exhaust gas. (2) The exhaust gas purifying catalyst according to (1) above, wherein the first OSC material and the second OSC material are ceria-zirconia based composite oxides. (3) The exhaust gas purifying catalyst according to (1) or (2) above, wherein the catalytic metal is Rh. (4) The exhaust gas purifying catalyst according to any one of (1) to (3) above, wherein the catalyst layer consists of one layer. (5) The exhaust gas purifying catalyst according to any one of (1) to (4), wherein the upstream catalytic layer is formed in a range from the upstream end to 40% to 80% of the total length of the substrate, and the downstream catalytic layer is formed in a range from the downstream end to 40% to 80% of the total length of the substrate. Effect of the Invention

[0012] According to the present invention, it is possible to provide an exhaust gas purification catalyst which has improved OSC performance while maintaining exhaust gas purification performance. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of an exhaust gas purifying catalyst of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing one embodiment of an exhaust gas purifying catalyst of the present invention. [Diagram 3] 1 is a graph showing the relationship between the ACZ ratio in the upstream catalyst layer and OSC performance in an example. [Figure 4] 1 is a graph showing the relationship between the ACZ ratio in a downstream catalyst layer and OSC performance in an example. [Diagram 5] 1 is a graph showing the OSC performance of catalysts of comparative examples and examples in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Preferred embodiments of the present invention will now be described in detail.

[0015] The exhaust gas purifying catalyst of the present invention has a substrate and at least one catalyst layer formed on the substrate.

[0016] The substrate is not particularly limited, and any material generally used in exhaust gas purification catalysts can be used. Specifically, the substrate can be a honeycomb-shaped material having a large number of cells, such as cordierite (2MgO·2Al 2 O 3 5SiO 2 Heat-resistant ceramic materials such as alumina, zirconia, silicon carbide, etc., and metal materials made of metal foil such as stainless steel, etc. Of these, cordierite is preferred from the viewpoint of cost.

[0017] The catalyst layer is formed on a substrate. Exhaust gas supplied to the catalyst for exhaust gas purification comes into contact with the catalyst layer while flowing through the flow path of the substrate, and harmful components are purified. For example, CO and HC contained in the exhaust gas are oxidized by the catalytic function of the catalyst layer to water (H 2 O) and carbon dioxide (CO 2 ), and NOx is reduced by the catalytic function of the catalyst layer to nitrogen (N 2 )

[0018] The total length of the catalyst layer is not particularly limited from the viewpoints of appropriate purification of harmful components in exhaust gas, manufacturing costs, and freedom in equipment design, and can be, for example, 2 cm to 30 cm, preferably 5 cm to 15 cm, and more preferably about 10 cm.

[0019] The catalyst layer is composed of at least one layer. The catalyst layer is composed of, for example, one layer, two layers, three layers, or four layers, preferably one layer or two layers, and more preferably one layer. For example, when the catalyst layer is composed of two layers, an upper layer and a lower layer, the lower catalyst layer is formed on the substrate, and the upper catalyst layer is formed on the lower catalyst layer. Also, for example, when the catalyst layer is composed of three or more layers, the lowermost catalyst layer is formed on the substrate, and other catalyst layers are formed on it in order, as in the case where the catalyst layer is composed of two layers. In the present invention, the uppermost catalyst layer is composed of an upstream catalyst layer and a downstream catalyst layer, but in this specification, the upstream catalyst layer and the downstream catalyst layer are collectively referred to as one catalyst layer.

[0020] The uppermost catalyst layer is composed of an upstream catalyst layer formed on the upstream side of the exhaust gas flow direction and a downstream catalyst layer formed on the downstream side of the exhaust gas flow direction. The upstream catalyst layer and the downstream catalyst layer may be partially overlapped. When the upstream catalyst layer and the downstream catalyst layer are partially overlapped, either the upstream catalyst layer or the downstream catalyst layer may be the upper layer in the overlapping portion. When the upstream catalyst layer and the downstream catalyst layer are partially overlapped, preferably, the upstream catalyst layer is the lower layer and the downstream catalyst layer is the upper layer in the overlapping portion. The upstream catalyst layer is formed in a range of usually 40% to 80%, preferably 50% to 70% of the entire length of the substrate from the upstream end. The downstream catalyst layer is formed in a range of usually 40% to 80%, preferably 50% to 70% of the entire length of the substrate from the downstream end. In the exhaust gas purifying catalyst of the present invention, the upstream catalyst layer and the downstream catalyst layer do not completely overlap.

[0021] FIG. 1 shows an embodiment of the exhaust gas purifying catalyst of the present invention, which has a two-layered catalyst layer. As shown in FIG. 1, the exhaust gas purifying catalyst 10 has a substrate 11 and a two-layered catalyst layer 12 formed on the substrate 11. The catalyst layer 12 has a lower catalyst layer 13 formed on the substrate 11 and an upper (top) catalyst layer 14 formed on the lower catalyst layer 13. The upper catalyst layer 14 is made up of an upstream catalyst layer 15 and a downstream catalyst layer 16. In FIG. 1, the upstream catalyst layer 15 and the downstream catalyst layer 16 are formed in the range of about 50% of the entire substrate length from the upstream and downstream ends in the exhaust gas flow direction, respectively. In FIG. 1, the arrows indicate the exhaust gas flow direction.

[0022] Fig. 2 shows one embodiment of the exhaust gas purifying catalyst of the present invention, in which the catalyst layer is composed of one layer. As shown in Fig. 2, the exhaust gas purifying catalyst 20 has a substrate 21 and a catalyst layer 22 composed of one layer formed on the substrate 21. The catalyst layer 22 is composed of an upstream catalyst layer 23 and a downstream catalyst layer 24. In Fig. 2, the upstream catalyst layer 23 and the downstream catalyst layer 24 are formed in a range from the upstream and downstream ends in the exhaust gas flow direction, respectively, to about 60% of the entire length of the substrate. In Fig. 2, the arrows indicate the exhaust gas flow direction.

[0023] The uppermost catalyst layer includes a catalyst metal, a first OSC material having a pyrochlore structure, and a second OSC material having an oxygen absorption and release rate faster than the first OSC material.

[0024] The catalytic metal may be a conventional catalytic metal used in exhaust gas purification catalysts, and may be any metal in the platinum group or an alloy mainly made of any metal in the platinum group. Examples of the platinum group metal include rhodium (Rh), platinum (Pt), palladium (Pd), ruthenium (Ru), iridium (Ir), and osmium (Os), with Rh being preferred. When the OSC material contains, for example, cerium (Ce), the catalytic activity of Rh decreases significantly with the increase in the amount of the OSC material, and therefore the effect of efficiently using the OSC material is great.

[0025] In the uppermost catalyst layer, two types of OSC materials are used in combination: a first OSC material having a pyrochlore structure, and a second OSC material having a faster oxygen absorption / release rate than the first OSC material.

[0026] OSC materials are inorganic materials with oxygen storage capacity. They store oxygen when lean exhaust gas is supplied and release the stored oxygen when rich exhaust gas is supplied. Examples of OSC materials include ceria (CeO 2 Among the above OSC materials, ceria (CeO 2 )-zirconia (ZrO 2 It is preferable to use a composite oxide based on the above-mentioned Cr-based oxide.

[0027] The first OSC material is an OSC material having a pyrochlore structure. OSC materials having a pyrochlore structure generally have the property of having a slow oxygen absorption / release rate but a large oxygen absorption / release amount (hereinafter also referred to as the OSC amount).

[0028] The pyrochlore structure is a structure that contains two metal elements, A and B, where B is a transition metal element. 2B 2 O 7 It is indicated by A 3+ / B 4+ Or A 2+ / B 5+ It is a type of crystal structure consisting of a combination of the above, and occurs when the ionic radius of A is relatively small in the crystal structure of this composition. For example, the chemical formula of ceria-zirconia composite oxide with a pyrochlore structure is Ce 2 Zr 2 O 7 In the pyrochlore structure, Ce and Zr are regularly arranged with oxygen between them. In addition, some of the metal elements A and B in the pyrochlore structure may be replaced by additional elements.

[0029] The first OSC material having a pyrochlore structure has a slower oxygen absorption / release rate than the second OSC material, and can still release oxygen even after the second OSC material has released all of its oxygen. In other words, the first OSC material having a pyrochlore structure can still exhibit oxygen absorption / release ability even after the peak of oxygen absorption / release by the second OSC material has passed. This is believed to be because the OSC material having a pyrochlore structure has a complicated crystal structure and has a complicated path for absorbing and releasing oxygen. More specifically, the total amount of oxygen released from 10 seconds to 120 seconds after the start of oxygen release is, for example, 60% to 95%, preferably 70% to 90%, and more preferably 75% to 85%, of the total amount of oxygen released from immediately after the start of oxygen release (0 seconds) to 120 seconds (100%).

[0030] As the first OSC material, it is preferable to use a ceria-zirconia composite oxide. The ceria-zirconia composite oxide may be a ceria-zirconia composite oxide made of ceria and zirconia, and may contain an additional element other than cerium (Ce) and zirconium (Zr). The additional element is not particularly limited, and may be, for example, a rare earth element other than cerium or an alkaline earth metal. Examples of rare earth elements other than cerium include praseodymium (Pr), scandium (Sc), yttrium (Y), lanthanum (La), neodymium (Nd), samarium (Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), ytterbium (Yb), and lutetium (Lu). From the viewpoint of high heat resistance and sufficient oxygen absorption and release ability from a low temperature, Pr, La, Nd, and Y are preferable, and Pr is particularly preferable. Examples of alkaline earth metal elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra), with Mg, Ca, and Ba being preferred. The total content of the additional elements in the first OSC material, calculated as oxides, is usually 10 mass% or less, and preferably 5 mass% or less, relative to the total mass of the first OSC material. The mass ratio of ceria to zirconia in the ceria-zirconia composite oxide is, for example, 10:1 to 1:10, preferably 5:1 to 1:5, and more preferably 2:1 to 1:2.

[0031] On the other hand, the second OSC material is an OSC material that has a faster oxygen absorption / release rate than the first OSC material. The second OSC material has a faster oxygen absorption / release rate but a smaller amount of oxygen absorption / release compared to the first OSC material having a pyrochlore structure. The second OSC material, for example, has a crystal structure different from that of the first OSC material, and a specific example of the crystal structure of the second OSC material is a fluorite structure.

[0032] As the second OSC material, it is preferable to use a ceria-zirconia composite oxide. The ceria-zirconia composite oxide may be a ceria-zirconia composite oxide made of ceria and zirconia, and may contain additional elements other than cerium (Ce) and zirconium (Zr). The additional elements are not particularly limited, and include, for example, rare earth elements other than cerium and alkaline earth metals. Examples of rare earth elements other than cerium include praseodymium (Pr), scandium (Sc), yttrium (Y), lanthanum (La), neodymium (Nd), samarium (Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), ytterbium (Yb), and lutetium (Lu). Among them, Pr, La, Nd, and Y are preferable from the viewpoint of high heat resistance and sufficient oxygen absorption and release ability from low temperatures, and La, Nd, and Y are particularly preferable. Examples of alkaline earth metal elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra), and among these, Mg, Ca, and Ba are preferred. The ceria-zirconia composite oxide may further contain aluminum (Al) as an additional element. In one embodiment, the second OSC material contains alumina (Al) in addition to ceria and zirconia. 2 O 3 ), Lantana (La 2 O 3 ), neodymia (Nd 2 O 3 ), yttria (Y 2 O 3 The total content of the additional elements in the second OSC material, calculated as oxides, is usually 50 mass% or less, preferably 40 mass% or less, based on the total mass of the second OSC material. A ceria-zirconia composite oxide containing alumina, lanthana, neodymia and yttria usually contains 20 mass% to 40 mass% of alumina and 1 mass% to 10 mass% of lanthana, neodymia and yttria. The mass ratio of ceria to zirconia in the ceria-zirconia composite oxide is, for example, 10:1 to 1:10, preferably 5:1 to 1:5, and more preferably 3:1 to 1:3.

[0033] The uppermost catalyst layer may contain any other components in addition to the above-mentioned catalyst metal, first OSC material, and second OSC material. The other components are not particularly limited, and examples thereof include metal oxides. Examples of the metal contained in the metal oxide include one or more metals selected from groups 3, 4, and 13 of the periodic table and lanthanoid metals. When the metal oxide is composed of oxides of two or more metals, it may be any of a mixture of two or more metal oxides, a composite oxide containing two or more metals, or a mixture of one or more metal oxides and one or more composite oxides.

[0034] The metal oxide may be, for example, an oxide of one or more metals selected from scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), neodymium (Nd), samarium (Sm), europium (Eu), lutetium (Lu), titanium (Ti), zirconium (Zr) and aluminum (Al), and is preferably an oxide of one or more metals selected from Y, La, Nd, Zr and Al. Examples of the metal oxide include alumina (Al 2 O 3 It is preferable to use a composite oxide containing alumina. The composite oxide containing alumina is preferably a composite oxide containing at least one selected from alumina, zirconia, lanthana, neodymia, and yttria, and more preferably a composite oxide of alumina and lanthana, and a composite oxide of alumina, zirconia, lanthana, neodymia, and yttria. The metal oxide can also be used as a support for supporting a catalytic metal or an OSC material.

[0035] The exhaust gas purification catalyst of the present invention uses two types of OSC materials with different properties in an optimized ratio in the upstream catalyst layer and downstream catalyst layer of the uppermost catalyst layer, thereby making it possible to increase the utilization efficiency of the OSC materials and improve the OSC performance while maintaining the exhaust gas purification performance.

[0036] The uppermost upstream catalyst layer contains a catalyst metal, a first OSC material having a pyrochlore structure, a second OSC material having a faster oxygen absorption / release rate than the first OSC material, and may contain other components such as metal oxides, etc. The catalyst metal, first OSC material, second OSC material, and metal oxide are as described above for the uppermost catalyst layer.

[0037] In the uppermost upstream catalyst layer, the content of the catalyst metal is usually 0.05 g / L to 1.0 g / L, and preferably 0.05 g / L to 0.6 g / L, relative to the volume of the substrate.

[0038] In the uppermost upstream catalyst layer, the content of the first OSC material is usually 5 g / L to 50 g / L, and preferably 5 g / L to 40 g / L, relative to the volume of the substrate.

[0039] In the uppermost upstream catalyst layer, the content of the second OSC material is usually 10 g / L to 135 g / L, and preferably 10 g / L to 110 g / L, relative to the volume of the substrate.

[0040] In the uppermost upstream catalyst layer, the mass ratio of the second OSC material to the total mass of the first OSC material and the second OSC material is 0.55 to 0.73, preferably 0.65 to 0.73. In the present invention, for example, a mass ratio of 0.55 to 0.73 means that the mass ratio is 0.55 or more and 0.73 or less. In the upstream catalyst layer into which exhaust gas discharged from the engine directly flows, the exhaust gas concentration is high, so that a reaction is likely to occur. In the upstream catalyst layer, when the mass ratio of the second OSC material is 0.55 to 0.73, the OSC material can be used more efficiently and the catalyst can exhibit high OSC performance, compared to the case where the mass ratio of the second OSC material is outside this range.

[0041] The uppermost downstream catalyst layer contains a catalytic metal, a first OSC material having a pyrochlore structure, a second OSC material having a faster oxygen absorption / release rate than the first OSC material, and may contain other components such as metal oxides, etc. The catalytic metal, first OSC material, second OSC material, and metal oxide are as described above for the uppermost catalyst layer.

[0042] In the uppermost downstream catalyst layer, the content of the catalyst metal is usually 0.05 g / L to 1.0 g / L, and preferably 0.05 g / L to 0.6 g / L, relative to the volume of the substrate.

[0043] In the uppermost downstream catalyst layer, the content of the first OSC material is usually 5 g / L to 80 g / L, preferably 5 g / L to 30 g / L, and more preferably 5 g / L to 20 g / L, relative to the volume of the base material.

[0044] In the uppermost downstream catalyst layer, the content of the second OSC material is usually 3 g / L to 60 g / L, preferably 3 g / L to 35 g / L, and more preferably 3 g / L to 20 g / L, relative to the volume of the base material.

[0045] In the uppermost downstream catalyst layer, the mass ratio of the second OSC material to the total mass of the first OSC material and the second OSC material is 0.27-0.55, preferably 0.27-0.45. In the downstream catalyst layer, the exhaust gas concentration is low and the reaction is difficult to occur. When the mass ratio of the second OSC material in the downstream catalyst layer is 0.27-0.55, the OSC material can be used more efficiently and the catalyst can exhibit high OSC performance compared to the case where the mass ratio of the second OSC material is outside this range.

[0046] In the exhaust gas purification catalyst of the present invention, when the catalyst layer is composed of two or more layers, at least one catalyst layer other than the uppermost layer may contain a catalytic metal, but may also contain, for example, an OSC material, a metal oxide, etc. in addition to the catalytic metal.

[0047] The catalytic metal may be any conventional catalytic metal used in exhaust gas purification catalysts, and may be, without particular limitation, any metal in the platinum group or an alloy mainly made of any metal in the platinum group, etc. Examples of the platinum group metal include rhodium (Rh), platinum (Pt), palladium (Pd), ruthenium (Ru), iridium (Ir), and osmium (Os).

[0048] As the OSC material, for example, the first OSC material and the second OSC material described above can be used.

[0049] Examples of the metal contained in the metal oxide include one or more metals selected from Groups 3, 4, and 13 of the periodic table and lanthanoid metals. The metal oxide may be, for example, an oxide of one or more metals selected from scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), neodymium (Nd), samarium (Sm), europium (Eu), lutetium (Lu), titanium (Ti), zirconium (Zr), and aluminum (Al).

[0050] The catalyst layers other than the uppermost layer are usually formed over the entire length of the substrate, but may be composed of an upstream catalyst layer and a downstream catalyst layer, like the uppermost catalyst layer.

[0051] In a preferred embodiment, the exhaust gas purification catalyst of the present invention has a substrate and a catalyst layer consisting of one layer formed on the substrate, the catalyst layer containing a catalyst metal, a first OSC material (preferably a ceria-zirconia composite oxide) having a pyrochlore structure, and a second OSC material (preferably a ceria-zirconia composite oxide) having a faster oxygen absorption / release rate than the first OSC material, and the catalyst layer is composed of an upstream catalyst layer formed on the upstream side of the exhaust gas flow direction and a downstream catalyst layer formed on the downstream side of the exhaust gas flow direction, the mass ratio of the second OSC material to the total mass of the first OSC material and the second OSC material in the upstream catalyst layer is 0.55 to 0.73, and the mass ratio of the second OSC material to the total mass of the first OSC material and the second OSC material in the downstream catalyst layer is 0.27 to 0.55.

[0052] The exhaust gas purification catalyst of the present invention can be prepared by a method known to those skilled in the art. For example, a slurry containing components for each catalyst layer is coated on a substrate, and this process is repeated to prepare a catalyst having the desired number of catalyst layers. EXAMPLES

[0053] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to these examples.

[0054] <Preparation of catalyst> Raw materials used Material 1:Al 2 O 3 :1 mass%-La 2 O 3 , 99% by mass-Al 2 O 3 Material 2: Pyrochlore OSC material (first OSC material): 51 mass%-CeO 2 , 46% by mass-ZrO 2 , 3% by mass-Pr 2 O 3 Material 3: ACZ (second OSC material): 30% by mass-Al 2 O 3 , 20% by mass-CeO2 , 44% by mass-ZrO 2 , 2% by mass-La 2 O 3 , 2 mass%-Y 2 O 3 , 2% by mass-Nd 2 O 3 Material 4: AZ: 30% by mass - Al 2 O 3 , 60% by mass-ZrO 2 , 4% by mass-La 2 O 3 , 4% by mass-Y 2 O 3 , 2% by mass-Nd 2 O 3 Material 5: Rh nitrate: Rhodium nitrate Material 6: Rh / AZ: Material 5 with Rh supported on Material 4 Base material: 875cc (400 cells square, wall thickness 4mil) cordierite honeycomb base material

[0055] Preparation of material 2 (pyrochlore OSC material) The pyrochlore OSC material was prepared by adding CeO 2 51% by mass, ZrO 2 46% by mass and Pr 2 O 3 The composition was adjusted to 3% by mass.

[0056] Preparation of material 6 (Rh / AZ) Material 5 (0.45 g / L, Rh content) and material 4 were added in this order to distilled water with stirring, and the mixture was stirred for 10 minutes. After that, the mixture was fired in an electric furnace at 500° C. for 2 hours to obtain material 6.

[0057] Preparation of catalyst In distilled water, material 6, material 1, material 2, material 3 and Al 2 O 3 The binder was added and the materials were suspended by stirring for about 10 minutes to prepare slurries containing fixed amounts of materials 6 and 1 and different amounts of OSC materials 2 and 3.

[0058] To the substrate, a slurry containing a predetermined amount of Material 2 and Material 3 was poured into the range from the upstream end to 60% of the total length of the substrate. The unnecessary portion was blown off with a blower, and the material was coated on the substrate wall surface to form an upstream catalyst layer. Next, for the substrate on which the upstream catalyst layer was formed, a slurry containing a predetermined amount of Material 2 and Material 3 was poured into the range from the downstream end to 60% of the total length of the substrate. The unnecessary portion was blown off with a blower, and the material was coated on the substrate wall surface to form a downstream catalyst layer. Finally, after drying at 120°C for 2 hours in a dryer, it was calcined at 500°C for 2 hours in an electric furnace to prepare Catalysts No. 1 to 10. In the obtained catalysts, the coat lengths of the upstream catalyst layer and the downstream catalyst layer were each 60% of the total length of the substrate, and a part of the downstream catalyst layer overlapped a part of the upstream catalyst layer.

[0059] Table 1 shows the compositions of the OSC materials of the upstream catalyst layer and the downstream catalyst layer for Catalysts No. 1 to 10. In Table 1, the ACZ ratio refers to the mass ratio of ACZ to the total mass of ACZ and the pyrochlore OSC material. Also, each layer of the upstream catalyst layer and the downstream catalyst layer contains 10 g of Material 1 (Al 2 O 3 ) and 10 g of Material 6 (Rh / AZ). Note that in Table 1, Catalysts No. 3 and 4 are the catalysts of the examples, and Catalysts No. 1 to 2 and 5 to 10 are the catalysts of the comparative examples.

[0060]

Table 1

[0061] <Durability Test> For each of the prepared catalysts, a durability test was carried out using an actual engine. Specifically, in the durability test, each catalyst was respectively installed in the exhaust system of a V-type 8-cylinder engine, and the exhaust gas in each atmosphere of stoichiometric and lean was repeatedly flowed for a certain time (at a ratio of 3:1) for 50 hours at a catalyst bed temperature of 900°C.

[0062] <OSC Performance Evaluation> For each catalyst that underwent durability testing under the above conditions, an OSC performance evaluation was carried out using an actual engine. Specifically, each catalyst was attached to the exhaust system of an L-type 4-cylinder engine, and the catalyst was introduced at a gas temperature of 600°C, a gas amount of 20g / s, and an air-fuel ratio (A / F) of 15.1-14.1. 2 The amount of OSC was calculated from the sensor behavior.

[0063] The results of the OSC performance evaluation are shown in Figures 3 and 4. Figure 3 shows the relationship between the ACZ ratio in the upstream catalyst layer and OSC performance (shown as OSC amount in Figure 3) when the ACZ ratio in the downstream catalyst layer is constant (ACZ ratio = 0.73). The catalysts shown in Figure 3 are catalysts No. 9, No. 8, No. 7, No. 2, and No. 6, in order from the lowest ACZ ratio. On the other hand, Figure 4 shows the relationship between the ACZ ratio in the downstream catalyst layer and OSC performance (shown as OSC amount in Figure 4) when the ACZ ratio in the upstream catalyst layer is constant (ACZ ratio = 0.73). The catalysts shown in Figure 4 are catalysts No. 5, No. 4, No. 3, No. 2, and No. 1, in order from the lowest ACZ ratio.

[0064] As shown in Fig. 3, there is a preferred range for the ACZ ratio of the upstream catalyst layer to exhibit high OSC performance, and high OSC performance was observed when the ACZ ratio was in the range of 0.55 to 0.73. Here, in the OSC performance data shown in Fig. 3, the ACZ ratio of the downstream catalyst layer is 0.73, which is outside the specific range of the present invention, but since exhaust gas discharged from the engine directly flows into the upstream catalyst layer, it is considered that the OSC performance of the upstream catalyst layer is unlikely to be affected by the OSC material of the downstream catalyst layer. Therefore, it can be said that this preferred range of the ACZ ratio of the upstream catalyst layer is a preferred range for any ACZ ratio of the downstream catalyst layer.

[0065] Furthermore, as shown in FIG. 4, there is a preferable range for the ACZ ratio in the downstream catalyst layer to exhibit high OSC performance, and high OSC performance was exhibited when the ACZ ratio was in the range of 0.27 to 0.55.

[0066] As shown in Figures 3 and 4, a catalyst with an ACZ ratio in the upstream catalyst layer in the range of 0.55 to 0.73 and an ACZ ratio in the downstream catalyst layer in the range of 0.27 to 0.55 exhibits high OSC performance. In the upstream catalyst layer, where the exhaust gas discharged from the engine flows directly, the exhaust gas concentration is high and the reaction is likely to occur. In the downstream catalyst layer, the exhaust gas concentration is low and the reaction is unlikely to occur. In this way, by using two types of OSC materials with different oxygen absorption / release speeds and oxygen absorption / release amounts in the upstream catalyst layer and downstream catalyst layer with different reactivity and optimizing the ratio in each layer, the OSC material can be efficiently used and the catalyst can exhibit high OSC performance.

[0067] FIG. 5 shows the OSC performance of the catalysts of the comparative example and the example. Catalyst No. 10, which corresponds to a conventional product, was used as the comparative example, and catalyst No. 4 was used as the example. The catalyst of the comparative example has the same total content of OSC material in each layer of the upstream catalyst layer and the downstream catalyst layer as the catalyst of the example, but the ACZ ratio is different. As shown in FIG. 5, the catalyst of the example, in which the ACZ ratio of each layer of the upstream catalyst layer and the downstream catalyst layer is optimized, showed higher OSC performance than the catalyst of the comparative example, in which the ACZ ratio of each layer of the upstream catalyst layer and the downstream catalyst layer is constant. In addition, since the total content of OSC material in the catalyst is the same for the catalyst of the example and the comparative example, it is considered that the exhaust gas purification performance is equivalent. [Explanation of symbols]

[0068] 10. Exhaust gas purification catalyst 11 Base material 12 Catalyst layer 13 Lower catalyst layer 14 Upper catalyst layer 15 Upstream catalyst layer 16 Downstream catalyst layer 20. Exhaust gas purification catalyst 21 Base material 22 Catalyst layer 23 Upstream catalyst layer 24 Downstream catalyst layer

Claims

1. A catalyst for purifying exhaust gas, comprising a substrate and at least one catalyst layer formed on the substrate, the uppermost catalyst layer includes a catalyst metal, a first OSC material having a pyrochlore structure, and a second OSC material having a fluorite structure and having a faster oxygen absorption / release rate than the first OSC material, and is composed of an upstream catalyst layer formed on the upstream side in the flow direction of the exhaust gas, and a downstream catalyst layer formed on the downstream side in the flow direction of the exhaust gas; in the upstream catalyst layer, a mass ratio of the second OSC material to a total mass of the first OSC material and the second OSC material is 0.55 to 0.73; in the downstream catalyst layer, a mass ratio of the second OSC material to a total mass of the first OSC material and the second OSC material is 0.27 to 0.55; The catalytic metal is Rh; Catalyst for purifying exhaust gas.

2. 2. The exhaust gas purifying catalyst according to claim 1, wherein the first OSC material and the second OSC material are ceria-zirconia based composite oxides.

3. 3. The exhaust gas purifying catalyst according to claim 1, wherein the catalyst layer consists of one layer.

4. The exhaust gas purifying catalyst according to any one of claims 1 to 3, wherein the upstream side catalytic layer is formed in a range from an upstream end to 40% to 80% of the entire length of the substrate, and the downstream side catalytic layer is formed in a range from a downstream end to 40% to 80% of the entire length of the substrate.

Citation Information

Patent Citations

  • Control device and exhaust emission control device of internal combustion engine

    JP2011111922A

  • Exhaust emission control device

    JP2013130146A

  • Exhaust gas purification catalyst

    JP2019084467A

  • Exhaust-purifying catalyst

    JP2022135562A